Jean Bruller, dessinateur et illustrateur de la littérature coloniale pour la jeunesse de l’entre-deux-guerres : de Loulou chez les nègres (1929) à Baba Diène et Morceau-de-Sucre (1937) - Nathalie Gibert-Joly (Strenae)
This article highlights the evolution of the various stances taken against colonialism by cartoonist Jean Bruller, the future writer known as Vercors (1902-1991), in the interwar period. The 121 Appeal that Vercors signed without hesitation in 1960 publicly proclaiming the right to insubordination in the Algerian war, and his fight in favor of the country’s independence since 1955 could lead us to a retrospective misinterpretation, that of a man and a myth of anti-colonial resistance from the beginning of his adulthood and in his artistic career, acting as a vehicle for this line of thought. The illustrations he provided for children's literature between the wars, and one of his personal creations, prove, on the contrary, that the cartoonist switched from an unconscious acceptance of colonialism to a critical questioning, between the beginning of the 1920s and the end of the 1930s. From Loulou chez les nègres to Baba Diène and Morceau-de-Sucre, we can distinguish three moments, marked by the publication of key works, in order to understand Jean Bruller's gradual awareness, visible in his collaborative choices as well as in the relationship between the text and his drawings. It is necessary to situate him in a time that was as much personal as historical: that of a young man in a certain educational and social milieu, sufficiently attuned to the world to have the means to emancipate himself from it; that of an artist with symbolic and economic realities, influenced by social networks corresponding to some of his ideals; and that of artists and writers who question themselves, and of intellectuals who took increasingly clear-cut positions during those years.